CARICOM existing and potential exports to Cuba, the CARICOM positive and negative lists, the Cuban MFN rate, and cuban positive list : a draft report - Gonzales, Anthony Peter ([s.n.] [S.l.], 2000)
Makes some comparisons between CARICOM existing and potential exports with the proposed CARICOM Positive List 1 A and the Negative List and the Cuban Positive List on an HS8 digit level and compares these three lists.